2001
DOI: 10.1161/hc37t1.094853
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Functional Recovery of Stunned and Hibernating Segments After Surgical Revascularization

Abstract: Background-Recovery of function is possible in patients with ischemic cardiomyopathy when left ventricular dysfunction is caused by stunning or hibernation. It is plausible that recovery of function after revascularization may take a longer time in hibernating myocardium compared with stunned myocardium. Accordingly, the time courses of functional recovery in hibernating and stunned myocardium were compared. Methods and Results-Patients (nϭ26) with ischemic cardiomyopathy undergoing surgical revascularization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
1
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(127 citation statements)
references
References 18 publications
8
109
1
9
Order By: Relevance
“…21 In contrast, in patients with abnormal wall motion before CABG, bypass surgery is expected to improve systolic wall motion by increasing the blood supply to hibernating myocardium. 22,23 In the present study, a ≥5% increase in ejection fraction was found in 34% of the patients. Although careful assessments were not undertaken in a considerable number of patients before CABG, 24 the results of the present study suggest that if the indications for CABG are determined from a thorough evaluation of myocardial ischemia, cardiac function, and myocardial viability using gated SPECT, this revascularization procedure will result in improved cardiac function in many patients.…”
Section: Discussionsupporting
confidence: 55%
“…21 In contrast, in patients with abnormal wall motion before CABG, bypass surgery is expected to improve systolic wall motion by increasing the blood supply to hibernating myocardium. 22,23 In the present study, a ≥5% increase in ejection fraction was found in 34% of the patients. Although careful assessments were not undertaken in a considerable number of patients before CABG, 24 the results of the present study suggest that if the indications for CABG are determined from a thorough evaluation of myocardial ischemia, cardiac function, and myocardial viability using gated SPECT, this revascularization procedure will result in improved cardiac function in many patients.…”
Section: Discussionsupporting
confidence: 55%
“…Dotyczy to zwłaszcza tych osób, u których przedoperacyjne badania obrazowe wskazywały na obecność niedokrwionego lub zahibernowanego mięśnia sercowego [291,292]. U większości pacjentów ze znacznym zmniejszeniem LVEF bezpośrednio po przebyciu STEMI obserwuje się istotną poprawę czynności skurczowej po 3 miesiącach [286].…”
Section: Zalecenia Dotyczące Optymalnej Strategii Postępowaniaunclassified
“…Contrary to hibernating myocardium [10], the stunned myocardium could have more acute change from transiently impaired coronary blood flow [11]. As long as the ischemic myocardium remains viable, the LV dysfunction can be partially or completely restored to normal by improving blood flow or by reducing oxygen demand.…”
Section: Discussionmentioning
confidence: 99%